Analisis Konsumsi Bahan Bakar Kegiatan Coal Getting Terhadap Produksi Batubara PT Banyan Koalindo Lestari Musi Rawas Utara Sumatera Selatan: Analysis of Fuel Consumption of Coal Getting Activities on Coal Production of PT Banyan Koalindo Lestari North Musi Rawas South Sumatra - Rulisfia Khalisyah Putri; Franto; Edwin Harsiga (Program Studi Teknik Pertambangan Universitas Bangka Belitung, 2026)
This study determines actual fuel ratio September and October, calculates cost wasteful fuel consumption, analyzes the factors fuel ratio, and recommends increasing production and fuel ratio efficiency. Primary data cycle time top loading and bottom loading Sany 365Hpro Excavator and Howo NX380 Dump Truck, secondary data fuel ratio plan, actual working hours, and fuel consumption in September and October. The actual fuel ratio value exceeds the fuel ratio plan September 0.508 liters/ton with difference 0.204 liters/ton and October 0.498 liters/ton with difference 0.115 liters/ton. Fuel costs Rp. 128,701,980 in September and Rp. 55,541,132 in October. Factors of the fuel ratio top loading or bottom loading, causing lost opportunities September 5168.25 MT/Month and October 5774.72 MT/Month. Use the same excavator coal cleaning and general activities causes lost time coal getting. Lose opportunity coal cleaning and general activity September 7278.99 MT and October 10115.98 MT. Top loading recommendations for coal getting resulted greater productivity. Using PC Komatsu 200 and shifting coal cleaning and general activity working hours to effective working hours increased production September 37063.03 MT and October 32605.08 MT. Fuel ratio decreased September 0.408 liters/ton with cost efficiency of Rp. 46,685,029.5, while October 0.344 liters/ton with cost efficiency of Rp. 55,541,132.